Effect of different priming methods in rice (Oryza sativa) - Subedi, R; Maharjan, BK; Adhikari, R (Journal of Agriculture and Environment, 2015)
Good germination of rice is considered critical for the plant life cycle. A laboratory experiment was conducted in IAAS, Lamjung campus, Sundarbazar to study the effect of different priming methods in rice. The experiment was done in completely randomized design using 12 treatments replicated thrice. The treatments consisted; Control (No priming), Hydro priming (soaking of seeds in distilled water for 72 hrs), PEG6000 - 5% and 10%, CaCl2 – 0.5% and 1%, KCl – 2% and 4%, KNO3 – 1% and 2% and NaCl – 1.8% and 3.6% where seeds were soaked for 12 hours followed by 12 hours drying. Both hydro priming and PEG improved germination energy, germination index, germination speed, radical length, and plumule length. The effect due to varied doses were not observed in the priming substances except PEG 6000, where PEG6000 – 5% was better as compared to PEG – 10% in overall observations.